Referências cefalométricas tridimensionais da simetria dentoesquelética - Porto, Olavo Cesar Lyra (2012)
Objective: To evaluate dentoskeletal symmetry in cone beam computed tomography (CBCT) scans of Brazilian individuals with Angle class I malocclusion. Materials and methods: Forty seven patients (22 girls) aged 11 to 16 years (14 years) seen in a private radiology service (CIRO, Goiânia, GO, Brazil). All the CBCT images were acquired from January 2009 to December 2010. Cephalometric measurements were made by multiplanar reconstructions (axial, coronal and sagittal) using Vista Dent3DPro 2.0 (Dentsply GAC, New York, USA). The minimum, maximum, mean and standard deviation values were described in tables, and the Student t test was used to define statistical significance (p<0.05). Results: Data were homogeneous, and the differences between right and left sides were not significant. Conclusion: The cephalometric measures of Brazilian individuals with Angle class I malocclusion can be used to define facial symmetry and three-dimensional standard references, which might be useful for orthodontic and surgical planning.